ESD tests on 850 nm GaAs-based VCSELs. (September 2016) - Vanzi, M.; Mura, G.; Marcello, G.; Xiao, K.
Abstract: Forward and reverse HBM, MM, CDM ESD tests have been performed on 850-nm VCSELs, together with EOS and overpower test. The physical analysis of the tested devices showed a variety of damages not easily correlated to the measured electro-optical degradations. The solution requires the detailed interpretation of the observed physical mechanism, by means of electron microscopy and device modelling. Highlights: Various ESD and EOS transient tests have been applied to commercial 850 nm, GaAs-based VCSELs Physical investigation has been extensively carried out by planar and cross-sectional STEM imaging on 1 μm thick lamellas Two damage types combine, involving or the inner annular boundary of the optical window, or the external oxidized areas. Several failure modes have been correlated to the observed damage Some physical damage is not detected by screening criteria, pointing towards ESD-induced latency and reliability risks.